Rapid assessment o f water eutrophic state in Tien Yen-Ha Coi Bay by estimating Chlorophyll-a concentration using geostatistical interpolations and MODIS data - Nguyen, Thi Thu Ha (ĐHQGHN, 2017)
Eutrophications is a natural process of enrichment o f water by nutrients, how ever in many case is considered as one of the major factors of water pollution affecting coastal ecosystem. Selection and application o f suitable indicator and method to assess sea eutrophicationis utmost important. This study aim sat clarifying water euứ ophic state m Tien Yen - Ha Coi B ay using geostatistical methods o f 40 in situ sites data and auxiliary information from MODIS/Terra image. Resultant predicted chlorophyll-a concentration distribution map in Tien Yen - Ha Coi Bay produced b y cokriging and eu ừ o p h ic possibility m ap com puted b y indicator kriging identified clearly that the b ay is classified as natural euừ ophic waters. B y this study, MODIS offers the possibility to support auxiliary information for assessment eutrophic state m large water areas. Cokrigmg and indicator kriging was proved to be effective for rapid environmental quality assessment and coastal water management.